2021
DOI: 10.3389/fonc.2021.738567
|View full text |Cite
|
Sign up to set email alerts
|

A Novel H2O2 Generator for Tumor Chemotherapy-Enhanced CO Gas Therapy

Abstract: Carbon monoxide (CO) gas therapy is a promising cancer treatment. However, gas delivery to the tumor site remains problematic. Proper tunable control of CO release in tumors is crucial to increasing the efficiency of CO treatment and reducing the risk of CO poisoning. To overcome such challenges, we designed ZCM, a novel stable nanotechnology delivery system comprising manganese carbonyl (MnCO) combined with anticancer drug camptothecin (CPT) loaded onto a zeolitic imidazole framework-8 (ZIF-8). After intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Keli Zhong et al devised a nanodrug delivery system (DDS) ( Fig. 7 A) for tumor chemotherapy and CO gas therapy [ 104 ]. They encapsulated a manganese carbonyl complex (MnCO) and the anticancer drug camptothecin (CPT) within a zeolite-type MOF (ZIF-8), resulting in the formation of a stable DDS named ZCM.…”
Section: Cornms Based On Hybrid Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keli Zhong et al devised a nanodrug delivery system (DDS) ( Fig. 7 A) for tumor chemotherapy and CO gas therapy [ 104 ]. They encapsulated a manganese carbonyl complex (MnCO) and the anticancer drug camptothecin (CPT) within a zeolite-type MOF (ZIF-8), resulting in the formation of a stable DDS named ZCM.…”
Section: Cornms Based On Hybrid Nanomaterialsmentioning
confidence: 99%
“…
Fig. 7 (A) A novel H 2 O 2 -triggered CO release MOF containing CORM and CPT for chemotherapy and gas therapy [ 104 ]. Copyright 2021, Frontiers Media S.A. (B) MOF based CORNM through activating the metal notes.
…”
Section: Cornms Based On Hybrid Nanomaterialsmentioning
confidence: 99%
“…Delivery of chemotherapeutic drugs by ZIF–8 for specific release in tumor tissues is one of the most widely used therapeutic approaches in cancer research ( Table 2 ) [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Interestingly, as many other nanomaterials have been demonstrated to elicit pro–death autophagy [ 83 , 84 ], Xu et al found that ZIF–8 induced PI3K–regulated death–promoting autophagy [ 9 ].…”
Section: Cancer Therapymentioning
confidence: 99%
“…Nanotechnology has developed rapidly in recent years, providing a good means to overcome the bottleneck problem of nonspecific and non-selective damage to body tissues caused by traditional therapies (e.g., chemotherapy, radiotherapy and immunotherapy), and exhibiting unique advantages in improving the effects of drugs and radiation therapy while reducing adverse reactions (44,(56)(57)(58). On the one hand, multifunctional nanocarriers can selectively transport therapeutic drugs by utilizing the difference between the tumor tissue and normal tissue to enhance drug permeability and retention.…”
Section: Smart Np-based Systems For Bc Treatment Based On the Tmementioning
confidence: 99%